The effects of self-care education based on the health literacy index on self-care and quality of life among menopausal women: a randomized clinical trial - Zahra Hossein Mirzaee Beni; Raziyeh Maasoumi; Shahzad Pashaeypoor; Shima Haghani (BMC, 2022)
Abstract Purpose Aging is associated with many different health-related challenges for women such as menopause and its associated problems. Self-care (SC) is a factor with potential effects on menopause and its consequences. SC education based on health literacy has the potential to improve menopausal women's SC. The aim of this study was to evaluate the effects of SC education based on the health literacy index (HLI) on SC and quality of life (QOL) among menopausal women. Methods This randomized clinical trial was conducted in Iran. Participants were 100 menopausal women purposively recruited from five comprehensive healthcare centers in the south of Tehran. They were randomly allocated to a control and an intervention group through block randomization. Intervention was an HLI-based SC education program implemented in four 1.5-hour weekly sessions through the lecture, group discussion, and question and answer methods. Data were collected before and eight weeks after the intervention using a demographic questionnaire, the Health Literacy for Iranian Adults scale, the Menopause-Specific Quality of Life Questionnaire, and the Menopausal Self-Care Questionnaire. The SPSS software (v. 22.0) was used to analyze the data through the Chi-square, Fisher's exact, paired-sample t, and the independent-sample t tests as well as the analysis of covariance at a significance level of less than 0.05. Findings There were no significant differences between the intervention and the control groups respecting the pretest mean scores of QOL (88.15 ± 32.36 vs. 79.6 ± 36.99) and SC (104.75 ± 12.31 vs. 103.32 ± 13.8) (P > 0.05). However, the posttest mean scores of QOL and SC in the intervention group significantly differed from the control group (66.44 ± 28.41vs. 81.3 ± 38.04 and 125.6 ± 11.23 vs. 102.6 ± 14.34) (P < 0.05). Conclusion HLI-based SC education is effective in significantly improving menopausal women's QOL and SC and can be used to improve health-related outcomes among menopausal women. Clinical trial registration This research was registered (24/03/2020) in the www.thaiclinicaltrials.org with registration number: TCTR20200324002.